Case Report: Lethal neonatal form of CPT II deficiency in consecutive pregnancies: fetal-neonatal characteristics, biochemical and molecular review - Tan, Y. Y.; Tewani, K. G.; Anand, A. J.; Kong, C. X.; Rajadurai, V. S.; Chandran, S. (Frontiers in Pediatrics, 2025)
Carnitine palmitoyltransferase II (CPT II) deficiency is a rare inherited disorder of mitochondrial oxidation of long-chain fatty acids (LCFA). Carnitine is the sole carrier of LCFA, which is transferred to the cellular mitochondria for β-oxidation; CPT II plays a vital role in this process. Three phenotypic forms of CPT II deficiency exist: lethal neonatal (LNF), severe infantile hepato-cardio-muscular, and mild adult myopathic forms. The LNF is the most severe type of CPT II deficiency. Management should be guided by shared decision-making with parents, taking into account the severity of the disease, the goals of care, and the quality of life for both the patient and their family. We present a consanguineous couple with two siblings in consecutive pregnancies with LNF of CPT II deficiency who exhibited similar symptoms, both antenatally and postnatally. Antenatal assessments revealed cardiomegaly, ventriculomegaly, and polycystic kidneys. The first sibling received all supportive measures, including extracorporeal life support, but succumbed. Parents, counseled antenatally by the perinatal palliative care team, opted for comfort care for the second sibling, who passed away on day 3 of life. Cardiac, renal, and cerebral malformations were consistent in fetal and neonatal ultrasound scans of both siblings, who had biochemical and molecular diagnoses, confirming CPT II deficiency. The fetal imaging signs served as reliable indicators for early diagnosis, especially in the background of consanguinity. We present the cases of the siblings, including a literature review on fetal and neonatal characteristics, as well as the biochemical and molecular features of CPT II deficiency.